Titanium Dioxide Nanoparticles Improve Growth and Enhance Tolerance of Broad Bean Plants under Saline Soil Conditions - Abdel Latef, Arafat Abdel Hamed; Srivastava, Ashish Kumar; El‐sadek, Mahmmoud Sayed Abd; Kordrostami, Mojtaba; Tran, Lam‐Son Phan (Land degradation & development, 2018)
Soil salinity is established as one of the major environmental problems, decreasing crop productivity worldwide, thereby threatening sustainable agriculture. In the present study, we evaluated the effects of titanium dioxide nanoparticles (nTiO2) for ameliorating soil salinity in broad bean, an important leguminous crop. As nTiO2 is known to have pro‐oxidant and antioxidant properties, the effects of three different nTiO2 concentrations (0·01%, 0·02% and 0·03%) were compared with respect to plant growth and stress responses. The 0·01% nTiO2 application significantly increased shoot length, leaf area and root dry weight of plants under normal conditions. These growth‐promoting effects were simultaneous with increased levels of chlorophyll b, soluble sugars and proline and enhanced activities of antioxidant enzymes. Under saline soil conditions, although proline level and enzymatic antioxidant activities were increased, plant growth significantly reduced. The 0·01% nTiO2 supplementation significantly increased the activities of enzymatic antioxidants and levels of soluble sugars, amino acids and proline in salt‐affected plants versus plants subjected to salinity alone. Thus, the increased antioxidant enzyme activities contributed to the observed reduction in hydrogen peroxide and malondialdehyde contents, while enhanced levels of proline and other metabolites contributed to osmoprotection, collectively resulting in significant plant growth improvement under salinity. Furthermore, nTiO2‐mediated positive effects were concentration dependent with 0·01% nTiO2 being the most effective, whereas 0·02% showed an intermediate response and 0·03% was almost ineffective under both control and saline soil conditions. Our findings provide a foundation for nTiO2 application in improving growth of plants cultivated on naturally contaminated saline soils. Copyright © 2017 John Wiley & Sons, Ltd.